Synchronous insight of in vitro and in vivo biological activities of Sambucus nigra L. extracts for industrial uses - Mota, Ana Henriques (2021)
There is a re-emerging interest in natural products as reputable sources of new active pharmaceutical ingredients. This study synchronously reports in vitro, with more than one cell line, and in vivo biological activities of extracts obtained from Sambucus nigra. Using several solvents and techniques, eighteen extracts were obtained from fresh and dried berries, and fresh flowers. The flavonoid content and identification were determined using HPLC-MS/MS. The extracts were then screened for antioxidant activity, total polyphenol content, collagenase, elastase, tyrosinase and acetylcholinesterase inhibition as well as photoprotection. In vitro and in vivo (murine model) anti-inflammatory activity and cytotoxicity (skin and monocytic cells) were also studied. The most promising extracts were those obtained from fresh flowers using either ultrasounds or methanol. These extracts showed similar results to positive controls, particularly the antioxidant activity (74.5 +/- 1.6 %), collagenase inhibition (93.6 +/- 0.6 %), photoprotection (Sun Protection Factor > 50), in vitro anti-inflammatory activity (96.9 +/- 2.9 %), as well as oral/topical anti-inflammatory activity. The ultrasounds/ethanol extract of fresh flowers presented higher collagenase inhibition (88.3 +/- 2.8 %) and in vitro anti-inflammatory activity (101.8 +/- 1.5 %). Cytotoxicity testing confirmed the safety. Chemical characterization allowed the deduction of a correlation between extract composition and biological activities, suggesting a straightforward application in the development of novel products subject to further investigation.